The Influence of Banking Risk Management on Financial Performance A Case Study of Core Capital Bank Group During and After Covid-19 - Jamaluddin; Jamothon Gultom; Noryani; Hasanudin; Ananda Hadistia; Yusran Daeng Matta (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The Core Capital Bank Group is a commercial bank with core capital ranging from < IDR6 trillion to > IDR70 trillion. The existence of this commercial bank is based on the bank's financial performance in each period. Banking risk management plays a crucial role in measuring bank financial performance, although financial performance is still below the expectations of commercial banksPurpose: This study aims to determine the effect of Banking Risk Management on the financial performance of a case study of the Core Capital Bank Group During and After Covid-19.Design/methodology/approach: This study uses descriptive statistical analysis and Panel Data Regression Equation that combines Cross Section and Time Series data with the selection of Random Effect Model (REM) Eviews 13. Data analysis is based on secondary data of Core Capital Commercial Banks with a sample of 14 Banks for the 2020-2024 period with a total of 70 observations.Findings/Results: The research findings show that Credit Risk and Operational Risk have a significant effect on financial performance. Operational Risk has the highest influence with a calculated t of -7.74 and a Prob value of 0.000 (p < 0.05) followed by Credit Risk with a calculated T of -6.02 and a Prob value of 0.000 (p < 0.05). Based on these findings, 2 recommendations are made: 1) Commercial Banks need to manage Credit Risk and Operational Risk so that bank financial performance remains stable. 2) Banks need to tighten their Creditworthiness analysis and the use of Sustainable Standard Operating Procedures.Conclusion: This study concludes that Credit Risk and Operational Risk are part of Banking risk management in improving the financial performance of Core Capital Bank Groups During and after Covid-19 which focuses on sustainable bank financial performance to foster public trust and long-term value for community stakeholders in banking.Originality/value (State of the art): This study contributes to the limited empirical literature on the financial performance of Core Capital Bank Groups based on Banking Risk Management during and after Covid-19 to address the challenges of the existence of commercial banks today amidst the rapid business competition in the banking industry in improving performance and providing services to their customers. Keywords:   bank risk management, core capital bank group, financial performance, panel data regression equation, random effect model